2019
DOI: 10.22460/project.v2i2.p175-180
|View full text |Cite
|
Sign up to set email alerts
|

Using Three Step-Interview to Improve Student’s Speaking Ability

Abstract: Speaking can be defined as an activity to share or discuss information that helped people to communicate with each other. To improve the students’ speaking learning interest, the teacher needs to recognize how to teach speaking effectively, and what instructional materials are the most appropriate for their students. The aims of the research are to find out whether or not teaching speaking using three – Step interview technique in improving students’speaking ability and to find out the teaching and learning si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
2
12
0
1
Order By: Relevance
“…The study showed that role play does improve speaking skills in terms of fluency, comprehension, context and interactive communication among students. The findings also showed and supported Aristy et al (2019) that role plays offer the potential for the development of knowledge of and about the target language, while fostering confidence in the students.…”
Section: Resultssupporting
confidence: 60%
“…The study showed that role play does improve speaking skills in terms of fluency, comprehension, context and interactive communication among students. The findings also showed and supported Aristy et al (2019) that role plays offer the potential for the development of knowledge of and about the target language, while fostering confidence in the students.…”
Section: Resultssupporting
confidence: 60%
“…Speaking skill is partly a reflection of someone whether he/she masters this language or not. Thus, it can be concluded that speaking as the most important skill of all four skills (Ur, 1996) cited in Aristy, Hadiansyah, & Apsari (2019). Liu, Xu (International Education Studies, v3 n1 p136-144 Feb 2010) English as a tool of communication has been playing an important part in acquiring cultural, scientific and technical knowledge, for collecting worldwide information and carrying out international exchange and cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity of speaking is concerned very few students get it. This condition has several causes (Aristy, Hadiansyah, and Apsari 2019). In this case, there are lots of students who lack of courage in speaking, especially Junior High School students since most of them have just started learning English, and also the limitedness of vocabulary and grammar skills in their speaking.…”
Section: Introductionmentioning
confidence: 99%